2021
DOI: 10.3390/ijerph18041818
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Psychosocial Barriers Affect the Active Commuting to University in Chilean Students

Abstract: Biking and walking are active commuting, which is considered an opportunity to create healthy habits. Objective: The purpose of this study was to determine the main environmental and psychosocial barriers perceived by students, leading to less Active Commuting (AC) to university and to not reaching the Physical Activity (PA) recommendations. Material and Methods: In this cross-sectional study, 1349 university students (637 men and 712 women) were selected. A self-reported questionnaire was applied to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…As green consciousness was recorded, active transport could also be promoted as an eco-friendly option. Female students proved to be more environmentally sensitive, confirming the literature, and the findings are in line with those of other scholars, suggesting that targeting women [21] and offering ample opportunities for developing environmentally focused interventions could increase active travel.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As green consciousness was recorded, active transport could also be promoted as an eco-friendly option. Female students proved to be more environmentally sensitive, confirming the literature, and the findings are in line with those of other scholars, suggesting that targeting women [21] and offering ample opportunities for developing environmentally focused interventions could increase active travel.…”
Section: Discussionsupporting
confidence: 88%
“…Being already physically active, this group engages in more physical activity on their own initiative either by habit, for health and physical status, or the high esteem of self-benefits from exercise. This research sheds light on whether active transport could meet the needs for more physical activity beyond academic obligations and whether gender differences are present, as the literature suggests for other faculty students [21].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For all of the above reasons, the purpose of this study was to evaluate the implementation of an urban bicycle programme for Chilean university students attending courses in Fundamental Formation of Self-Care and Healthy Lifestyle (SHL), as well as to promote instances of knowledge and use of the bicycle that favour an increase in its use as a means of transport, given that in Chilean reality there is a low level of use of bicycles [41].…”
Section: Bicycle Use By University Studentsmentioning
confidence: 99%
“…Similarly, in Brazil, active commuting was associated with low income in work population [ 29 ], but university students were not studied. In Chile, the university students revealed that personal factors were more influencing than environmental aspects to using active commuting [ 30 ].…”
Section: Introductionmentioning
confidence: 99%